Consecutive Interpreting Strategies on A Court Setting: A Study of English into Indonesia Interpretation - Heri Kuswoyo; Ayu Yeza Audina (Universitas Teknokrat Indonesia, 2020)
This study was an attempt to investigate the consecutive interpreting strategies used by an Indonesian interpreter, Yuliana Tansil, in the court setting. This study examined a trial court in English and consecutively interpreted it to Indonesian. Faerch and Kasper’s (1983) theory of consecutive interpreting strategy was used. The descriptive qualitative method was applied as the method of this study. Data were collected through video recording taken from official YouTube. The video then was transcribed carefully. The results showed that the interpreter used two types of consecutive interpreting strategies, namely reduction strategies, and achievement strategies. In terms of reduction strategy, the interpreter applied skipping, incomplete sentence, and filtering. Yet, the message abandonment was not found in this study. In terms of achievement strategies, the interpreter used both appeal for assistance and elaborate strategy. The results also indicated that the interpreter frequently elaborated and expanded the lexical meaning of words or phrases in the utterances. The interpreter used this strategy when she faced the difficult words in long utterances because of some cultural nuance. So, she elaborated on her understanding of the message by adding more information as a way of making the utterance in the target language to be understood better.